Analysis of Archival Transformation at X Institution in Bekasi City - Khalizah Alfi Fadhliyah; Christian Wiradendi Wolor; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research is motivated by the importance of archival transformation as an effort to increase the efficiency and effectiveness of archive management at Institution X Bekasi City. This research uses a qualitative descriptive method by describing and analyzing problems based on primary and secondary data collected through observation, interviews, documentation, as well as studies from books, previous research and related articles. This research aims to find out more deeply about the transformation of archives at Institution X Bekasi City which faces challenges in the manual archive management system. The results obtained from this research show that the archiving system at this institution is still very manual with processes for recording, storing and searching archives that are prone to loss, damage and are less efficient. Transforming archives through archive digitization is an urgent need to increase operational efficiency and archive security. The proposed digital transformation includes transferring archival media from physical to digital format using an e-archive application which is able to speed up the document search process, reduce the risk of damage, and maintain data security. Apart from that, this digitalization is also expected to support the operational sustainability of Institution X Bekasi City with a more modern and integrated archive system. The implementation of this technology not only overcomes physical limitations in document storage, but also facilitates faster access and transparency in archive management. Keywords: archival transformation; electronic filing system; institution X Bekasi City